Effects of caldera collapse on magma decompression rate: An example from the 1800 14C yr BP eruption of Ksudach Volcano, Kamchatka, Russia - Andrews Benjamin J.; Gardner James E. (Journal of Volcanology and Geothermal Research, 2010)
Caldera collapse changes volcanic eruption behavior and mass flux. Many models of caldera formation predict that those changes in eruption dynamics result from changes in conduit and vent structure during and after collapse. Unfortunately, no previous studies have quantified or described how conduits change in response to caldera collapse. Changes in pumice texture coincident with caldera formation during the 1800 14C yr BP KS1 eruption of Ksudach Volcano, Kamchatka, provide an opportunity to constrain magma decompression rates before and after collapse and thus estimate changes in conduit geometry. Prior to caldera collapse, only white rhyodacite pumice with few microlites and elongate vesicles were erupted. Following collapse, only gray rhyodacite pumice containing abundant microlites and round vesicles were erupted. Bulk compositions, phase assemblages, phenocryst compositions, and geothermometry of the two pumice types are indistinguishable, thus the two pumice types originated from the same magma. Geothermobarometry and phase equilibria experiments indicate that magma was stored at 100–125 MPa and 895 ± 5 °C prior to eruption. Decompression experiments suggest microlite textures observed in the white pumice require decompression rates of > 0.01 MPa s− 1, whereas the textures of gray pumice require decompression at ~ 0.0025 MPa s− 1. Balancing those decompression rates with eruptive mass fluxes requires conduit size to have increased by a factor of ~ 4 during caldera collapse. Slower ascent through a broader conduit following collapse is also consistent with the change from highly stretched vesicles present in white pumice and to round vesicles in gray pumice. Numerical modeling suggests that the mass flux and low decompression rates during the Gray phase can be accommodated by the post-collapse conduit developing a very broad base and narrow upper region.